Designing Information Systems for Transaction and Production Data Management A&N convection - Rosanna, Nadya; Hery, Hery; Widjaja, Andree E. (Pandawan Sejahtera Indonesia, 2021)
Many companies have implemented technology in conducting their business, one of them is by using information systems in managing their business. The business process that runs on the Konveksi A&N is still manual because the Konveksi A&N has not implemented or is familiar with information systems like other companies has. This causes all the data collection process of goods, production, and transactions are all documented in different books, making it possible for errors in recording and calculating the data. In addition, the owner also needs to come directly to the location to find out new data or updated data where this takes more time. This research aims to establish a web-based system that can make business processes in Konveksi A&N more effective. This web-based system will be built using a system development methodology in the form of a prototyping method that uses the Hypertext Preprocessor (PHP) programming language. System modeling was developed using UML 2.5, use case diagrams, activity diagrams, and class diagrams. The final result of this study is a website-shaped information system that can document all data contained in the Konveksi A&N such as the existence of a master data that contains all the data of convection, production data, and also transaction data to facilitate the owner in checking back all activities that are occurs in Konveksi A&N. There are also some reports about the transaction that can display information related to data contained in the system.